Advanced Level Practice Education: UK Critical Care Pharmacists' Opinions in 2015 - Ruth E. Warin; Richard S. Bourne; Mark Borthwick; Greg Barton; Ian Bates (MDPI AG, 2016)
National UK standards for critical care highlight the need for clinical pharmacists to practice at an advanced level and above. The aim of this research paper was to describe the views of UK critical care pharmacists on the current provision of Advanced Level Practice (ALP) education and accreditation. It sought to identify whether there is a need for a national or regional training programme. A questionnaire was delivered electronically targeting UK critical care pharmacists. Whilst the response rate was low at 40% (166/411); the views expressed were representative of UK practitioners with the majority of responders meeting the national specifications for clinical pharmacist staffing in critical care areas. The responses highlighted work-based learning as the main resource for developing ALP and a lack of suitable training packages. The vast majority of pharmacists identified that a national or regional training programme was required for ALP. The results also identified the main barriers to undertaking ALP accreditation were lack of time, uncertainty regarding the process and its professional benefits and a lack of education and training opportunities. In conclusion, the responses clearly indicated that, for the necessary progression of critical care pharmacists to ALP, a national or regional training programme is required.